2008
DOI: 10.1128/jcm.00848-08
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of Nasal and Rectal Swabs for Detection of Methicillin-Resistant Staphylococcus aureus Colonization in an Active Surveillance Program

Abstract: All medical and high-risk surgical patients were screened for methicillin-resistant Staphylococcus aureus colonization over 3.5 years. The sensitivities of nasal and rectal swabs were 68% and 62%, respectively. Naris and open-skin-site swabs detected 467 (74%) of 627 adult carriers identified. Rectal swabs detected an additional 160 (26%) carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
1
19
2
Order By: Relevance
“…We found that cultures of samples from the nares and cultures of combined samples from the nares and groin have similar sensitivities (91% and 98%, respectively) but that determinations based on the combined samples increased the negative predictive value from 58% to 88%, confirming other investigations suggesting that cultures of multiple body sites should be used to rule out MRSA colonization (2,3,5,6,12). The sensitivity determined in our study with cultures of samples from the nares and groin was higher than that previously reported (85% sensitivity) (9) but was similar to the sensitivities reported by others for studies using cultures of samples from the nares and groin (96% sensitivity) (21), nares and rectum (96% sensitivity) (5), and nares and perineum (87% to 90% sensitivity) (3,9).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…We found that cultures of samples from the nares and cultures of combined samples from the nares and groin have similar sensitivities (91% and 98%, respectively) but that determinations based on the combined samples increased the negative predictive value from 58% to 88%, confirming other investigations suggesting that cultures of multiple body sites should be used to rule out MRSA colonization (2,3,5,6,12). The sensitivity determined in our study with cultures of samples from the nares and groin was higher than that previously reported (85% sensitivity) (9) but was similar to the sensitivities reported by others for studies using cultures of samples from the nares and groin (96% sensitivity) (21), nares and rectum (96% sensitivity) (5), and nares and perineum (87% to 90% sensitivity) (3,9).…”
supporting
confidence: 84%
“…The number of body sites colonized with MRSA and colonization of the groin correlate with the degree of environmental contamination in patient rooms (13). Studies have measured yields of MRSA cultures of different body sites (2,3,5,6,11,15,19). However, few studies have assessed differences in quantities of MRSA at different sites (14).…”
mentioning
confidence: 99%
“…These data suggest that screening of multiple body sites may provide better diagnostic accuracy data and improve rates of detection [31,34]. Whether the increased sensitivity of screening multiple body sites translates into a measurable effect on MRSA reduction needs to be shown [36,37]. Indeed, several studies suggest that nasal screening alone can already provide enough data to decrease hyperendemic MRSA rates [12,18].…”
Section: Active Screening Of Mrsa Carriers: Universal or Targeted?mentioning
confidence: 87%
“…Detection of MRSA colonization in patients is enhanced when body sites in addition to the anterior nares are cultured, including the pharynx, open wounds, skin, respiratory secretions, and the rectum or stool. 33,34 We performed surveillance cultures for MRSA and VRE from single body sites only but used broth enrichment and extended incubation to enhance the sensitivity of our culture methods. 19,20 This probably explains why the prevalence of colonization at the time of ICU admission in this trial was 15% higher for MRSA and 64% higher for VRE than that reported previously.…”
Section: Discussionmentioning
confidence: 99%